EVALUATING THE THERAPEUTIC POTENTIAL OF PRP THERAPY IN KNEE JOINT PAIN MANAGEMENT: A LARGE-SCALE STUDY - DR SUDHEER DARA , MBBS MD, FIAPM, DR. MINAL CHANDRA MBBS, DA, DNB(ANAESTHESIA), F-IAPM, DR. CHETANA CHETAN (South Eastern European Journal of Public Health, 2025)
Background: Degenerative conditions are the primary causes of chronic knee joint pain and pose a major challenge for long-term management. Platelet-Rich Plasma (PRP) therapy, based on autologous growth factors, has attracted attention as an alternative to conventional treatments. Methods: This is a randomized controlled trial where the efficacy and safety of PRP therapy in 1,000 patients suffering from knee joint pain were assessed over a follow-up period of four to five years. Patients were divided into two groups: PRP and placebo (saline), with treatments administered at the initial visit and at one and two months. Results: The VAS and WOMAC score of the PRP group showed significant and sustained improvements over the placebo group, and the results were obvious to last longer. Even though minor adverse events like pain and swelling at the injection site were found to occur more in the PRP group, they have been manageable. Conclusion: With a long period, PRP therapy proved to be effective for reducing the pain and improving the functionality of the joints offering an upward, long-term benefit for chronic knee pain management. Strong results from the study support the wide clinical application of PRP, which can significantly enhance the quality of life in patients.